2020
DOI: 10.1037/cep0000202
|View full text |Cite
|
Sign up to set email alerts
|

Social monkeys learn more slowly: Social network centrality and age are positively related to learning errors by capuchin monkeys (Cebus [Sapajus] apella).

Abstract: The cognitive demand on animals to learn, maintain, and remember the complexities of social relationships is theoretically higher for individuals who live more complex social lives. Previous research has suggested that both across and within species, the cognitive ability to flexibly learn and manipulate information may increase with increased social complexity. In this study, we determined the relationship between social complexity and cognitive performance on 2 related tests of general learning: associative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Berhane and Gazes (2020) found that older and more central individuals made more errors in the learning tasks. While this study does indeed show a relationship between cognition and sociality Berhane and Gazes (2020) caution that future work should test specific cognitive abilities that are theoretically predicted to be linked to species-specific ecology and fitness. In a related topic, social interactions between dogs and humans, Meyers-Manor and Botten (2020) test domestic dogs in the wild - that is, their owners’ homes.…”
Section: Contributionsmentioning
confidence: 93%
See 3 more Smart Citations
“…Berhane and Gazes (2020) found that older and more central individuals made more errors in the learning tasks. While this study does indeed show a relationship between cognition and sociality Berhane and Gazes (2020) caution that future work should test specific cognitive abilities that are theoretically predicted to be linked to species-specific ecology and fitness. In a related topic, social interactions between dogs and humans, Meyers-Manor and Botten (2020) test domestic dogs in the wild - that is, their owners’ homes.…”
Section: Contributionsmentioning
confidence: 93%
“…In their subjects, socially house brown capuchin monkeys ( Cebus apella ), learning scores extracted from a principal components analysis were predicted by both age and social network centrality - just not in the predicted direction! Berhane and Gazes (2020) found that older and more central individuals made more errors in the learning tasks. While this study does indeed show a relationship between cognition and sociality Berhane and Gazes (2020) caution that future work should test specific cognitive abilities that are theoretically predicted to be linked to species-specific ecology and fitness.…”
Section: Contributionsmentioning
confidence: 93%
See 2 more Smart Citations
“…Lastly, and group dynamics notwithstanding, certain individuals are simply more likely to seek out and use social information than others, and certain individuals are likely better able to learn new skills than others, due to demographic, social, and personality factors (e.g., [175][176][177]-see [178] for a comprehensive discussion of this topic). Of course, within a captive setting, the physical environment may also constrain the transmission of social information, as discussed in Hopper [5].…”
Section: Individual and Species Differencesmentioning
confidence: 99%